Compassionate love in romantic relationships: A review and some new findings. (August 2014) - Fehr, Beverley; Harasymchuk, Cheryl; Sprecher, Susan
Compassionate love has been identified as one of the major types of love experienced in relationships (Berscheid, 2010), but one that has been overshadowed by the study of romantic love. In this article, we review research on compassionate love, a relative newcomer to the close relationships field, and present findings that more fully flesh-out the nature of the experience of this kind of love. We begin by discussing conceptions and measurement of compassionate love. We then present a study on the relation between compassionate love and love styles, with a focus on distinguishing between compassionate love and the agape (altruistic) love style. The literature on individual differences in compassionate love is discussed next. The spotlight then shifts to research on the link between compassionate love and prosocial relationship behaviors, relationship quality, and relationship stability. Differences between compassionate love given versus received also are highlighted. We end with a discussion of what compassionate love "looks like" in the context of a romantic relationship and recommend directions for future research.